Analisis Pengaruh Beberapa Faktor Terhadap Pendapatan Petani Padi di Subak Guama Desa Selanbawak Kecamatan Marga Kabupaten Tabanan - Rastana, I Dewa Gede; Guna, I Nyoman Ariana; Rusdianta, I Gede Made; Sarjana, I Wayan Mula (Universitas Tabanan, 2024)
Subak Guama, located in Desa Selanbawak, Kecamatan Marga, Kabupaten Tabanan, has experienced fluctuations and declines in farmer incomes from 2020 to 2023. This study aims to analyze the effects of land area, harvest costs, and credit received by farmers, both partially and simultaneously, on the income of rice farmers in Subak Guama. Primary data was collected through questionnaires, with 84 rice farmers selected as samples using the Slovin formula. The data was analyzed using multiple linear regression with the help of SPSS. The results of the study show that land area has a significant and positive effect on the income of rice farmers in Subak Guama. Similarly, harvest costs and credit also have significant and positive impacts on farmer income. Simultaneous testing reveals that the variables of land area, harvest costs, and credit collectively have a significant effect on the income of rice farmers in Subak Guama, Desa Selanbawak, Kecamatan Marga, Kabupaten Tabanan. These findings highlight the importance of these factors in influencing farmer income, suggesting that improvements in land management, efficient harvest costs, and access to credit could provide economic benefits to farmers.